2017
DOI: 10.1080/14786419.2017.1408094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Agave americana L. on the human, and Aspergillus oryzae S2 α-amylase inhibitions

Abstract: Among phenolic compounds, Agave americana L. extract contained puerarin (38.4%) and p-coumaric acid (12.29%) (pCa). From the Lineweaver-Burk plots, pCa and puerarin demonstrated a competitive and a non competitive inhibitions towards human α-amylase activity, respectively. PCa exhibited a higher human inhibitory activity with an IC of 98.8 μM which was about 2.3 times than acarbose. Puerarin (IC = 3.87 μM) and pCa (IC = 10.16 μM) also showed an excellent inhibition for Aspergillus oryzae S2 α-amylase activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…In the study of Zhao and Zhou, GLUT4 transposition under insulin stimulation and puerarin intervention was observed by an immunofluorescence method. Their result confirmed that the transposition obstacle did happen in the free fatty acid (FFA)-induced IR model of 3T3-L1 lipocytes and that puerarin showed a promoting effect on GLUT4 transposition [ 25 ].…”
Section: Effect Of Puerarin On Glucose and Lipid Metabolismmentioning
confidence: 73%
“…In the study of Zhao and Zhou, GLUT4 transposition under insulin stimulation and puerarin intervention was observed by an immunofluorescence method. Their result confirmed that the transposition obstacle did happen in the free fatty acid (FFA)-induced IR model of 3T3-L1 lipocytes and that puerarin showed a promoting effect on GLUT4 transposition [ 25 ].…”
Section: Effect Of Puerarin On Glucose and Lipid Metabolismmentioning
confidence: 73%
“…Puerarin and apigenin isolated from this species showed greater inhibitory effects against A. oryzae α-amylase, while p-coumaric acid proved a major inhibitor to human α-amylase at IC 50 : 98.8 µM, with an inhibition rate 2.3 times higher than acarbose. Thus, isolated flavonoids may be used as therapeutic agents for postprandial glycemia [52,53].…”
Section: Polar Compounds: Phenols and Flavonoidsmentioning
confidence: 99%
“…Free fructose was determined by directly measuring the extract, and total fructose was determined by measuring the hydrolyzed extract. Once the inulin content was measured, inulin yield in the extract was determined with Equation (3).…”
Section: Characterization Of the Vegetable Materials And Soluble Matter Extraction Conditionsmentioning
confidence: 99%
“…A variety of Ecuadorian endemic plants were traditionally used due to their medicinal properties, among which jicama (Smallanthus sonchifolius) and cabuya (Agave americana) [1][2][3]. From these Andean species, some autochthonous products have been obtained, for example, "Tshawar mishki" (also known as "agua miel" or honey water), jicama syrup and cabuya syrup [4][5][6].…”
Section: Introductionmentioning
confidence: 99%